Vitamin B12 deficiency and sublingual and intramuscular treatment: case report (Research, Society and Development, 2022)
Vitamin B12 is an essential micronutrient for some metabolic processes. It is not synthesized by the body and is obtained from foods of animal origin. Its deficiency is frequent and can cause dermatological, hematological and neurological disorders. The deficiency must be diagnosed early and treatment started as soon as possible. There are oral, sublingual and intramuscular treatments and the choice should be based on the severity of the deficiency and factors that interfere with the absorption of this micronutrient. Objective this study is to report a case of a patient with vitamin B12 deficiency and the differences found by intramuscular and sublingual treatments. This is a case report in which laboratory data were collected in the reports of a private clinical analysis laboratory between the years 2019 to 2022. The patient presented vitamin B12 deficiencies in the years 2019 and 2022. In the year 2019, the patient was treated with intramuscular injections. In the year 2022, she was treated with sublingual pills. There were differences between the two interventions in post-treatment vitamin B12 dosage. The two treatments used by different routes proved to be efficacious, but the intramuscular treatment was more effective than the sublingual treatment. The investigation of vitamin B12 deficiency is an important conduct in the evaluation of patients, since early diagnosis can prevent neurological and hematological disorders, as well as provide a better quality of life. Each case must be evaluated to indicate the most appropriate treatment and restore normal vitamin parameters.